Associations of children's lung function with ambient air pollution: joint effects of regional and near-roadway pollutants. Issue 6 (19th November 2013) - Urman, Robert; McConnell, Rob; Islam, Talat; Avol, Edward L; Lurmann, Frederick W; Vora, Hita; Linn, William S; Rappaport, Edward B; Gilliland, Frank D; Gauderman, W James
Abstract : Background: Previous studies have reported adverse effects of either regional or near-roadway air pollution (NRAP) on lung function. However, there has been little study of the joint effects of these exposures. Objectives: To assess the joint effects of NRAP and regional pollutants on childhood lung function in the Children's Health Study. Methods: Lung function was measured on 1811 children from eight Southern Californian communities. NRAP exposure was assessed based on (1) residential distance to the nearest freeway or major road and (2) estimated near-roadway contributions to residential nitrogen dioxide (NO2 ), nitric oxide (NO) and total nitrogen oxides (NOx ). Exposure to regional ozone (O3 ), NO2, particulate matter with aerodynamic diameter <10 µm (PM10 ) and 2.5 µm (PM2.5 ) was measured continuously at community monitors. Results: An increase in near-roadway NOx of 17.9 ppb (2 SD) was associated with deficits of 1.6% in forced vital capacity (FVC) (p=0.005) and 1.1% in forced expiratory volume in 1 s (FEV1 ) (p=0.048). Effects were observed in all communities and were similar for NO2 and NO. Residential proximity to a freeway was associated with a reduction in FVC. Lung function deficits of 2–3% were associated with regional PM10 and PM2.5 (FVC and FEV1 ) and with O3 (FEV1 ), but not NO2 across the range of exposure between communities. Associations with regional pollution and NRAP were independent in models adjusted for each. The effects of NRAP were not modified by regional pollutant concentrations. Conclusions: The results indicate that NRAP and regional air pollution have independent adverse effects on childhood lung function.